The Adjacency Pairs Patterns of Trumps’ Victory Interview in ‘60 Minutes’ - Bintana, Khomsa; Rukmini, Dwi; Sofwan, Ahmad (Universitas Negeri Semarang, 2018)
This research is descriptive qualitative research which focuses on adjacency pairs patterns of Trumpsâ€™ victory interview in â€™60 Minutesâ€™. The objectives of this study are to analyze the patterns realization of adjacency pairs in the interview, to evaluate the adjacency pairs contribution of the conversation flow in the â€œ60 Minutesâ€, and to evaluate the pedagogical contribution. The subject of the research are Lesley Stahl, Donald Trump, Melania Trump, Donald Trump Jr, Eric Trump, Ivanka Trump, and Tiffani Trump. The writer collected the data through observation and documentation. There are two data collections that had been analyzed in this research. The data collection are the video of the interview and the transcription of the interview. The writer found some research results. First, there are six patterns of adjacency pairs found in this research. The following details are 45 data of question patterns, 17 data of assertion patterns, 7 data of request patterns, 4 data of assessment patterns, 1 data of compliment pattern, and 1 data of invitation pattern. The dominant data is the question patterns and the least data is the compliment and invitation patterns. The second is the contribution of conversation flow. Almost all the responses given by the speakers are preferred responses, so the conversation runs smoothly. Although, there are some dispreferred responses given but it does not decrease the meaning of the conversation. It gives effective contribution to the flow of the conversation. The third is this research has contribution to the theoretical and practical aspects. The theoretical contribution implicated to the theory development of linguistic especially conversation analysis and adjacency pairs. Meanwhile in practical contribution, this research can be used as reference in teaching English especially speaking.